Examining the gender gap: academic performance disparity in regional and national examinations in Dessie city administration, Ethiopia - Amogne Asfaw Eshetu; Simret Alemu; Aster Mulat; Aminat Abdu; Bezawit Gobezie; Enatnesh Muluken; Asemach Anagaw; Elsabet Mulugeta; Ehite Hailemariam; Sewasew Aragaw (Discover Education)
Abstract Girls' education significantly benefits communities and countries. Despite ongoing efforts, gender disparity in developing countries remains a persistent issue. This study aimed to investigate gender disparity in regional and national examinations using an ex-post facto research design. To achieve this, we analyzed the scores of 3,349 students in the regional examination and 2,722 students in the national examination, all of whom were enrolled in the regular program for the 2022/2023 academic year in the Dessie city administration. Independent samples t-tests, Chi-square tests, and simple linear regression assessed the gender disparity in academic performance. The results of the study showed statistically significant academic performance differences in both the regional examination [t(3347) = 2.812, p < 0.05 for average score and t(3347) = 3.179, p < 0.05 for percentile respectively] with modest effect; and national in examination t(2720) = 8.599, p < 0.01) with moderate effect favoring male students. The chi-square test output revealed that the proportion of female students was below expected in the top-achieving groups (χ2 (1) = 22.41, p < 0.05) and higher than expected in the bottom groups (χ2 (1) = 6.451, p < 0.05 in the national examination. No statistically significant proportion difference was found in the regional examination in either the top or bottom achieving groups. A chi-square test of independence comparing the proportion of failed and passed students in regional examination revealed a significant interaction (χ2 (1) = 5.652, p < 0.05) where the proportion of failed female students was higher than expected, and the proportion of passed female students was lower than expected as compared with males. The simple leaner regression model also confirmed sex as a determinant of academic performance. The result showed that extra efforts remain to address the gender gap in academic performance. We recommend that parents, school administrators, teachers, female students, and the government further strengthen the interventions to narrow the gender gap.